HUBUNGAN PENGETAHUAN ORANG TUA TENTANG CARA MERAWAT GIGI ANAK DENGAN KEJADIAN KARIES GIGI PADA ANAK DI PAUD MAKKAH DESA KALIORI KECAMATAN KALIBAGOR KABUPATEN BANYUMAS TAHUN 2014 - Susilo Rini; Ina Lusiana (Viva Medika, 2016)
Poor dental care is one of the factors that influence the occurrence of dentalcaries. Preliminary study of the incidence of dental caries in children in mekkahplaygroup is higher than mulia bangsa playgroup. The high percentage ofincidence of dental caries in children do Mekkah Playgroup can not be separatedfrom a lack of parental knowledge about how to care for your child’s teeth, sothey do not control the type of food / snacks are eaten by children and do not getchildren to brush their teeth regularly every day.The study aims to determine the relationship of parental knowledge about how tocare for your child's teeth with dental caries incidence in children in MakkahPlaygroup Kaliori Kalibagor Village District of Banyumas city in 2014.The method used is analytic survey with cross sectional approach. This study usesprimary data in the form of answers to questionnaires maternal knowledge abouthow to care for your child's teeth and observations on the incidence of dentalcaries in children. The study population of all parents of children in MakkahPlaygroup Kaliori Kalibagor Village District of Banyumas city in 2014 as manyas 52 people. The study sample as many as 52 people were taken to the totalsampling. Data analysis using chi square test.Parents of children with early childhood knowledge about how to care for yourteeth Makkah children mostly in the category of pretty much as 25 people(48.1%). Children of Makkah Playgroup mostly experienced dental caries asmany as 34 children (65.4%). There is a relationship of parental knowledge abouthow to care for your child's teeth with dental caries incidence in children ofMakkah Playgroup Kaliori Kalibagor Banyumas City in 2014 (p = 0.008).Knowledge of parents about how to care for your child's teeth associated with theincidence of dental caries in children of Makkah Playgroup Kaliori KalibagorBanyumas city in 2014. Keywords: Knowledge, Toots Care, dental caries